KERAGAMAN JENIS RAYAP PADA KEBUN MONOKULTUR KAKAO DI HUTAN PENDIDIKAN UNIVERSITAS TADULAKO SULAWESI TENGAH - Zulkaidhah, Zulkaidhah; Hapid, Abdul; Ariyanti, Ariyanti (ForestSains, 2017)
This research had the objectives  to find out  examine the structure and the termite community monoculture cocoa gardens. The research was conducted from March 2016 to May 2016 in Education Forest of Tadulako University  area around the village 0f Bukit Makmur, Bolano Lambunu Subdistrict, Parigi Moutong Regency. The observation of termites was conducted using transect method. Parameters observed were environmental parameters, and microclimate. The total diversity of termite species found was 7. the biomass of Nekromass on the monoculture cocoa  system was 0.92 Mg/ha, and litter was 7 Mg/ha. Plants in the garden is dominated by cocoa as a staple crop, undergrowth found 20 species. microclimate at the study site, the average soil temperature, air temperature, humidity and the soil moisture content were 23.82 ° C,  24.29 ° C, 78.11%, and 39.28% respectively.